Immersion and distance in fictional worlds - Thomas Pavel (Itinéraires)
Based on the notion of immersion as developed by Jean-Marie Schaeffer, the article examines the readers’ relationship with fictional worlds. It compares the temporal succession of the exposition, the knot, the adventures, and the denouement of a plot with the spatial effects of visual perspective in a painting. The reader or spectator easily adopts the maxims governing fictional characters and the space of Goods within which they act. Immersion doesn’t however prevent the reader from discovering, beyond these maxims and Goods, their intangible source, which is also the source of aesthetic wonder.